Pengaruh Ketimpangan Ekonomi Dan Pemahaman Ekonomi Islam Terhadap Minat Mengembangkan 212 Mart Dengan Ghirah Sebagai Variabel Intervening - Hilyati Inayah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2018)
This study aims to determine the effect of economic inequality and Islamic economic understanding on the interest in developing 212 Mart with ghirah as an intervening variable. The method used in this study is a quantitative research method by taking a sample of 65 people from 212 Mart investors. The method of data analysis uses path analysis. The results showed that economic inequality had no effect on ghirah and interest in developing 212 Marts, whereas Islamic economic understanding had a positive and significant effect on ghirah and interest in developing 212 Mart